Maternal post-natal tobacco use and current parental tobacco use is associated with higher body mass index in children and adolescents: an international cross-sectional study. - Braithwaite, Irene (2015)
Background: We investigated whether maternal smoking in the first year of life or any current parental smoking is associated with childhood or adolescent body mass index (BMI). Methods: Secondary analysis of data from a multi-centre, multi-country, cross-sectional study (ISAAC Phase Three). Parents/guardians of children aged 6-7 years completed questionnaires about their children's current height and weight, whether their mother smoked in the first year of the child's life and current smoking habits of both parents. Adolescents aged 13-14 years completed questionnaires about their height, weight and current parental smoking habits. A general linear mixed model was used to determine the association between BMI and parental smoking. Results: 77,192 children (18 countries) and 194 727 adolescents (35 countries) were included. The BMI of children exposed to maternal smoking during their first year of life was 0.11 kg/m 2 greater than those who were not (P = 0.0033). The BMI of children of currently smoking parents was greater than those with non-smoking parents (maternal smoking: +0.08 kg/m 2 (P = 0.0131), paternal smoking: +0.10 kg/m 2 (P < 0.0001)). The BMI of female adolescents exposed to maternal or paternal smoking was 0.23 kg/m 2 and 0.09 kg/m 2 greater respectively than those who were not exposed (P < 0.0001). The BMI of male adolescents was greater with maternal smoking exposure, but not paternal smoking (0.19 kg/m 2 , P < 0.0001 and 0.03 kg/m 2 , P = 0.14 respectively). Conclusion: Parental smoking is associated with higher BMI values in children and adolescents. Whether this is due to a direct effect of parental smoking or to confounding cannot be established from this observational study.